Penciptaan Souvenir Jam Dinding Ornamen Karo Berbahan Dasar Kayu dengan Teknik Ukir - Jimmi Micael Ginting; Misgiya Misgiya (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study presents a woodcraft creation in the form of a wall clock with traditional Karo ornaments as the main visual element. The creation is driven by the urgency to preserve the visual culture of the Karo people, which is increasingly threatened by modernization, and the lack of distinctive local souvenirs in tourist areas such as Berastagi, which often offer only generic or mass-produced items. This creation aims not only to function as an indicator of time but also as a medium for cultural preservation, education, and the strengthening of the Karo visual identity in a contemporary context. The creative process applies the